Yield loss due to leaf spot and pod blight disease complex in rainfed blackgram (Phaseolus mungo) dominated by Cercospora cruenta relative to meteorological parameters - BHARDWAJ, C L; THAKUR, D R (The Indian Journal of Agricultural Sciences, 2013)
A field experiment conducted during 5 wet season during 1993-97 over 6 environments each year to investigate theyield loss relationship of leaf spol and pod blight disease complex with mean weekly weather parameter at pre-flowering and past-flowering revealed that leaf spot and pod blight disease complex dominated by Cercospora cruenla Sacco The 1 July sown gave highest grain yield of'PDU I' blackgram both in protected (624 kg/ha) and unprotected (393 kg/hal plots. The interaction effect of sowing dates and plant protection was not significant. The relationship of this interaction at preflowering with maximum temperature (30.25Â°C) was negative and significant (-0.982*) indicating that rise in temperature would result in decrease in yield. Contrarily, maximum relative humidity of 90.70% (+0.931 **)and rain frequency of 2.95 days/week (+0.786**) had significant positive correlation. Interestingly, all the parameters were significantly and negatively correlated at post-flowering crop period indicating that a small degree of rise or fall in these parameters would significantly reduce the yield both under protected and unprotected disease management. Reduced rainfall and its frequency at post-flowering seemed to contribute to low yield of black gram with delayed Sowing.